IMPLEMENTASI BIMBINGAN KEAGAMAAN BAGI NARAPIDANA BERAGAMA ALIRAN KEPERCAYAAN TRIDHARMA - Manulang, Johanes Gabe Saputra; Kadaryanto, Bagio; Harahap, Irawan (LPPM STIH Awang Long, 2024)
The observance of religious practices for inmates adhering to the Tridharma faith in Bagansiapiapi City based on Law No. 6 of 2013 has not been properly implemented, as the facilities for religious practices of other faiths are not equal to those already existing. The purpose of this research is to analyze the implementation of religious guidance for inmates adhering to the Tridharma faith in Bagansiapiapi City based on Government Regulation Number 32 of 1999 on terms and procedures for the implementation of the rights of correctional inmates, and to analyze the obstacles and efforts to overcome these obstacles in the implementation of religious guidance for inmates adhering to the Tridharma faith in Bagansiapiapi City. The method used is sociological legal research. Based on the research results, it is known that the implementation of religious guidance for inmates adhering to the Tridharma faith in Bagansiapiapi City has not been fully realized, as some inmates have not fully received the necessary religious guidance. This results in some inmates not receiving the spiritual support they need. Government Regulation Number 32 of 1999 on terms and procedures for the implementation of the rights of correctional inmates emphasizes the importance of fulfilling the rights of inmates, including the right to receive religious guidance.